EFEKTIVITAS METODE EXTENDING CONCEPT THROUGH LANGUAGE ACTIVITIES (ECOLA) DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS SISWA KELAS X SMA NEGERI 1 ENREKANG - H. Abu Bakar Tumpu; Jumriati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abstract: Effectiveness of Extending Method Concepts Through Language Activities (Ecola) inImproving Reading Comprehension Skills of Texts of Class X Students of High School 1Enrekang. This study aims to examine the effectiveness of the Extending Concept Method ThroughLanguage Activities (ECOLA) in Improving Reading Comprehension Skills for Class X Students ofEnrekang 1 High School and to examine the effectiveness of student learning outcomes by usingExtending Concept Method Through Language Activities (ECOLA) with conventional models inimproving refined text reading skills. The type of research used is a quantitative approach with methodexpriment. The research variable consists of two, namely the application of the Extending Conceptstrategy method through Language Activities (ECOLA) as an independent variable (X) and learning towrite letters as dependent variables (Y). The research design used in this study was experimentalresearch using a quasi-experimental method with the initial test design and final test of the control groupand experimental group with random samples (Therandomized pretest-posttest control grouf design. Theresults of this study indicate Extending Concept methods Through Language Activities ( ECOLA) iseffective in improving the reading skills of text comprehension in class X students of SMA Enrekang 1and there are differences in the effectiveness of student learning outcomes by using the ExtendingConcept method Through Language Activities (ECOLA) with conventional models in improvingreading comprehension skills.